Standardisation of laboratory animals for biomedical research in Poland - Szymańska, Hanna (Radiology and oncology (Ljubljana), 2001)
Increasing demands for biomedical research require laboratory animals of good quality. Simultaneously, the scientists aim at limiting the number of sacrificed laboratory animals. Some international organisations like ICLAS, FELASA, SOLAS deal with the promotion of proper breeding and care of laboratory animals. In 199T The Animal Protection Act' was adopted by Polish Parliament. The standardisation of laboratory animals for biomedical research in Poland is the main task of the Commission on Biology of Laboratory Animals P.A.Sci. and Polish National Committee for Collaboration with ICLAS. In 2000, the Department of Genetics and Laboratory Animal Breeding, M. Sklodowska-CurieMemorial Cancer Center and Institute of Oncology in Warsaw wasdesigned as National Reference Centre for SPF Animal Breeding. The department consists of five integral parts: (1) bank of SPF (Specified Pathogen Free) inbred mouse and rat strains, (2) experimental animals laboratory, (3) health monitoring laboratory, (4) genetic laboratory, (5) anatomo-pathological laboratory. Trends in development of laboratory animal science in Poland and Europe are overlapping. The standardisation of laboratory animals according to international recommendation seems to be sufficient in leading centres.
Keywords: Animal husbandry; Animal rights; Animal testing alternatives; Animal welfare; Animals, laboratory; biomedicinske raziskave; laboratorijske živali; Poland; Poljska; zaščita živali; Žival, testiranje, alternative; Živali laboratorijske; Živali, zaščita; Živinoreja